Pengaruh Kompensasi terhadap Tingkat Keterlibatan Kerja (Work Engagement) Generasi Milenial - Shafwah, Salsabila; Clara, Cornellia (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study aims to analyze the influence of compensation on the level of work engagement among millennial employees. The research method used is quantitative, employing regression analysis and mediation testing using Process Macro Hayes in IBM SPSS. The study population comprises all millennial employees working in various companies in the Jakarta area, selected due to their significant presence in the current workforce and unique characteristics that influence work engagement. The sample was collected using purposive sampling technique with a total of 100 respondents, deemed representative of the millennial employee population in Jakarta. The results indicate that compensation has a positive and significant impact on work engagement among millennial employees. This finding suggests that increased compensation is correlated with higher work engagement. Mediation testing also reveals that job satisfaction mediates the relationship between compensation and work engagement, where adequate compensation enhances job satisfaction, which in turn boosts work engagement. Overall, this study highlights the importance of effective and fair compensation policies in enhancing motivation and work engagement among millennial employees. Employees who feel they receive fair and adequate compensation tend to be more engaged in their work, ultimately contributing to improved organizational performance.